Synthesis: Some thoughts on medieval culture and the task of the medieval philosopher - Snyman, J. J. (Koers, 1975)
The basic drive of the philosophical output of Prof J.A.L Taljaard can, to my mind, correctly be said to be found in the historiography of philosophy of his Dutch tutor, Prof D.H.T Vollenhoven. Vollenhoven characterizes post-medieval philosophy as anti-synthetic, in which two options can be taken: either anti-synthetically left or anti-synthetically right. The former rejects a synthesis between pagan philosophy and Christian doctrine (a synthesis which reached its heyday in Medieval Scholasticism), thereby also rejecting the significance of God’s Revelation for scientific endeavour. The option to the right also rejects the synthesis between pagan and Christian thought, but is bent upon finding and assigning a proper place to Word Revelation in scientific and cultural endeavour, thereby trying to break down the clerical restrictions forced upon the relevance of Scriptures to all sectors of human life. Against Scholasticism it should be maintained that Scriptures determine not only matters of faith and church life, but is also applicable to other spheres of life. This is exactly what Prof Taljaard wanted and still wants to be: antisynthetically right, a position recently termed by himself as New Right.